Três trajetórias e uma mesma estrada - Pereira, Odirlei Dias [UNESP]; Tolentino, Célia Aparecida Ferreira [UNESP] (My University, 2012)
The process of migration of the rural northeast workers toward the cities of the south of Brazil in search of work and better living conditions reached millions of individuals and constituted the basis of our industrialization and modernization, especially since the 1930s. The Cinema has not ignored this vast phenomenon and, as much as the literature put the question in debate, particularly since 1960, when our seventh art was assumed as part of the national intelligence. In this article, we observed three narratives that thematize the escape from rural to urban from the northeastern hinterland: Vidas Secas (1963), by Nelson Pereira dos Santos, Trópicos (BR / ITA, 1967), by Gianni Amico, and O Caminho das Nuvens (2003), by Vicente Amorim. Participants of the politicized cinema, Vidas Secas and Trópicos draw the political impasses of the period in the form of movies and in the aesthetic choices, trying to understand the role of these migrants in Brazilian life. Already in O Caminho das Núvens, performed four decades later, the narrative is assumed as part of the cinema of entertainment, thinking the process of migration as a choice, as stated the form of this artwork of the called cinema of the resumption.

O processo de migração do trabalhador rural nordestino em direção às cidades do sul do país, em busca de trabalho e melhores condições de vida, atingiu milhões de indivíduos e constituiu a base de nossa industrialização e modernização, sobretudo a partir dos anos de 1930. O cinema não passou ao largo deste vasto fenômeno e, tanto quanto a literatura, colocou em debate a questão, particularmente a partir de 1960, quando nossa sétima arte assumiu-se como parte da intelligentsia nacional. Neste artigo, observamos três narrativas que tematizam a fuga do rural para o urbano a partir do sertão nordestino: Vidas Secas (1963), de Nelson Pereira dos Santos, Trópicos (BR/ITA, 1967), de Gianni Amico, e O Caminho das nuvens (2003), de Vicente Amorim. Partícipes do cinema politizado, Vidas Secas e Trópicos desenham os impasses políticos do período na forma dos filmes e nas escolhas estéticas, procurando entender o papel destes migrantes na vida brasileira. Já em O Caminho das Nuvens, realizado quatro décadas mais tarde, a narrativa assume-se como parte do cinema de entretenimento, pensando a migração como escolha, tal como indica a forma desta obra do chamado cinema da retomada.
Three Paths in the Same Road
Keywords: cinema; migração e cinema; cinema e pensamento social